The observation and analysis of stellar photospheres - Gray, David F., 1938- (Cambridge : Cambridge University Press, 2008)
Gray describes the equipment, observational techniques and analysis used in the investigation of photospheres. The first half of the book develops the tools of analysis while the second half demonstrates how they can be applied.
1. Background -- 2. Fourier transforms -- 3. Spectroscopic tools -- 4. Light detectors -- 5. Radiation terms and definitions -- 6. The black body and its radiation -- 7. Radiative and convective energy transport -- 8. The continuous absorption coefficient -- 9. The model photosphere -- 10. The measurement of stellar continua -- 11. The line absorption coefficient -- 12. The measurement of spectral lines -- 13. The behavior of spectral lines -- 14. The measurement of stellar radii and temperatures -- 15. The measurement of photospheric pressure -- 16. Chemical analysis -- 17. Velocity fields in stellar photospheres -- 18. Stellar rotation -- Appendix A. A table of useful constants -- Appendix B. Physical parameters of stars -- Appendix C. A fast Fourier transform Fortran program -- Appendix D. Atomic data -- Appendix E. The strongest lines in the solar spectrum -- Appendix F Computation of random errors.
Reprint. Originally published: 2005.
Includes bibliographical references and index.
Keywords: Stellar photospheres -- Observations